Impact of human factor management on company productivity: the moderating effect of digitalization - Kuong Rodríguez Jorge Ulises; Arana Barbier Pablo José (Cogent Business & Management, 2024)
The purpose of this research was to study the impact of human factor management on company productivity, with digitalization as a moderating variable, with emphasis on medium and large companies in the services sector, in Lima, Peru. This research has a quantitative approach and cross-sectional design. The technique used was structural equation modeling with the maximum likelihood estimation method. The study was carried out with a sample of 330 people from the banking sector in the city of Lima, in Peru. For statistical analysis, Confirmatory Factorial Analysis, and hypothesis testings, the SPPS AMOS tool was used. A conceptual model based on Dynamic Capability View theory was developed that allows us to better understand the phenomenon of the impact of human factor management on the productivity of companies, under the moderating effect of digitalization. As the main conclusions of this research, it was found that there is a positive relationship between the human factor management and the company productivity; likewise, it was found that digitalization has a moderating effect in the relationship between human factor management and productivity, with the exception of the human factor performance appraisal. These findings contribute to the existing literature and debate, as well as, allow to determine which dimensions of human factor management can be enhanced under the impact of a digital environment, thus contributing better to business performance.
Keywords: 650; Human factor management; business performance; productivity; digitalization; industry 4.0